High performance Li-ion sulfur batteries enabled by intercalation chemistry. Issue 70 (27th July 2015) - Lv, Dongping; Yan, Pengfei; Shao, Yuyan; Li, Qiuyan; Ferrara, Seth; Pan, Huilin; Graff, Gordon L.; Polzin, Bryant; Wang, Chongmin; Zhang, Ji-guang; Liu, Jun; Xiao, Jie
Abstract : A new prototype of Li-ion sulfur battery with graphite as an anode has been demonstrated after successfully addressing the interface issue of graphite in an ether based electrolyte. Abstract : The unstable interface of lithium metal in high energy density Li sulfur (Li–S) batteries raises concerns of poor cycling, low efficiency and safety issues, which may be addressed by using intercalation types of anode. Herein, a new prototype of Li-ion sulfur battery with high performance has been demonstrated by coupling a graphite anode with a sulfur cathode (2 mA h cm −2 ) after successfully addressing the interface issue of graphite in an ether based electrolyte.